Engineering injectable vascularized tissues from the bottom-up: Dynamics of in-gel extra-spheroid dermal tissue assembly. (December 2021) - Feijão, Tália; Neves, Mariana I.; Sousa, Aureliana; Torres, Ana L.; Bidarra, Sílvia J.; Orge, Iasmim D.; Carvalho, Daniel T.O.; Barrias, Cristina C.
Abstract: Modular tissue engineering approaches open up exciting perspectives for the biofabrication of vascularized tissues from the bottom-up, using micro-sized units such as spheroids as building blocks. While several techniques for 3D spheroid formation from multiple cell types have been reported, strategies to elicit the extra-spheroid assembly of complex vascularized tissues are still scarce. Here we describe an injectable approach to generate vascularized dermal tissue, as an example application, from spheroids combining fibroblasts and endothelial progenitors (OEC) in a xeno-free (XF) setting. Short-term cultured spheroids (1 day) were selected over mature spheroids (7 days), as they showed significantly higher angiogenic sprouting potential. Embedding spheroids in fibrin was crucial for triggering cell migration into the external milieu, while providing a 3D framework for in-gel extra-spheroid morphogenesis. Migrating fibroblasts proliferated and produced endogenous ECM forming a dense tissue, while OEC self-assembled into stable capillaries with lumen and basal lamina. Massive in vitro interconnection between sprouts from neighbouring spheroids rapidly settled an intricate vascular plexus. Upon injection into the chorioallantoic membrane of chick embryos, fibrin-entrapped pre-vascularized XF spheroids developed into a macrotissue with evident host vessel infiltration. After only 4 days, perfused chimeric capillaries with human cells were present in proximal areas, showing fast and functional inosculation between host and donor vessels. This method for generating dense vascularized tissue from injectable building blocks is clinically relevant and potentially useful for a range of applications.